2019
DOI: 10.1177/1461444819828718
|View full text |Cite
|
Sign up to set email alerts
|

Online political efficacy and political participation: A mediation analysis based on the evidence from Taiwan

Abstract: Consensus on the impact of information-oriented use of social media on political participation is lacking. Some argue a positive relationship, in that social media promotes participation through awakening the user’s agency, while others focus on the selection and disenabling effects of low-quality content. Nevertheless, both arguments focus almost exclusively on the objective conditions for participation and largely ignore users’ motivations to participate. Consequently, this article proposes online political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…Other articles considered online political participation [62,68]. One study, applying causal mediation analysis to assess a causal mechanism [74], found that information-oriented social media use affects political participation, mediated or enabled through the user's online political efficacy [62]. Overall, our analysis found largely beneficial mobilizing effects for political participation across this set of articles.…”
Section: Effects On Key Political Variablesmentioning
confidence: 68%
See 2 more Smart Citations
“…Other articles considered online political participation [62,68]. One study, applying causal mediation analysis to assess a causal mechanism [74], found that information-oriented social media use affects political participation, mediated or enabled through the user's online political efficacy [62]. Overall, our analysis found largely beneficial mobilizing effects for political participation across this set of articles.…”
Section: Effects On Key Political Variablesmentioning
confidence: 68%
“…Common causal inference techniques that were used in our sample include instrumental variable designs that introduce exogenous variation in the treatment variable [56][57][58][59][60], matching approaches to explicitly balance treatment and control groups [61][62][63], and panel designs that account for unobserved confounders with unit and/or time fixed effects [64,65].…”
Section: Causal Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…Given that the concept of political efficacy is highly contextual, it should be adapted to the context and behavioral activities under study [76,77]. While some recent studies have employed specific efficacy measures targeted towards online behaviours (e.g., [22,70,78]), little is known about how different efficacy beliefs are related to specific participation patterns, especially when targeted towards a specific social or political issue. Therefore, drawing from the work of Velasquez & LaRose [79], this paper includes four different types of efficacy (internal political efficacy, collective cause efficacy, social media internal political efficacy, and social media collective efficacy), tailored to both the social media modes of action, as well as the issue movement in which the political actions are embedded.…”
Section: Political Efficaciesmentioning
confidence: 99%
“…Taiwanese citizens have high enthusiasm for political discussion and enjoy access to various social media (Freedom House, 2014; Skoric et al., 2016). Studies showed that social media use facilitated extensive political activities in Taiwan (Chen et al., 2016, 2019; Hsieh and Li, 2014; Su and Xiao, 2020). Political discussion has also elicited greater engagement, such as lobbying and mobilizing campaigns (Hsieh and Li, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%